An exploratory study on strengthening and thermal stability of magnetron sputtered W nanoparticles at the interface of Cu/Ni multilayer films. (October 2020) - Schoeppner, R.L.; Mohanty, G.; Polyakov, M.N.; Petho, L.; Maeder, X.; Michler, J.
Abstract: An initial study to investigate the effect of controlled deposition of nanoparticles at multilayer interfaces was conducted to explore the mechanical effect of particles on laminate structures. Nanoparticles with diameter of about 4.5 nm were specifically deposited at the interface between Cu and Ni laminates by forced agglomeration of magnetron sputtered ions using a Mantis Ltd. Nanogen50 nanoparticle generator and the hardness of these films were measured using the nanoindentation technique. Cu/Ni laminates without W nanoparticles have an average modulus value of approximately 120 ± 3.7 GPa and hardness value of 2.23 ± 0.07 GPa, while the hardness values of the particle-containing films are greater, regardless of particle density. The areas with the lowest particle density at the interfaces (0.9 at.% W) show the greatest increase in hardness, with an increase of about 1.3 GPa greater than the particle-free sample. However, as the particle density increases, there is a corresponding decrease in hardness. In-situ x-ray diffraction of these films was also conducted to observe the annealing behavior of these films. For all samples, the Cu and Ni layered structure remained intact; however, there is evidence of Ni diffusion along grain boundaries and interaction with the oxygen, likely creating NiO. After annealing, a significant number of the W nanoparticles dissolved into the Ni matrix to create NiW solid-solution. The ability to deposit particles with such precise control has the potential to open up an exciting new field of research. Graphical abstract: Unlabelled Image